2020
DOI: 10.1371/journal.pone.0233857
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of geriatric syndromes in older adults

Abstract: Introduction The geriatric syndromes of frailty, sarcopenia, weight loss, and dementia are highly prevalent in elderly individuals across all care continuums. Despite their deleterious impact on quality of life, disability, and mortality in older adults, they are frequently under-recognized. At Saint Louis University, the Rapid Geriatric Assessment (RGA) was developed as a brief screening tool to identify these four geriatric syndromes. Materials and methods From 2015-2019, the RGA, comprised of the FRAIL, SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 28 publications
6
53
0
5
Order By: Relevance
“…The FRAIL screen has been integrated with 3 other tests: The SARC-F (Sarcopenia) ( 2 , 73 ), the Simplified Nutrition Appetite Questionnaire (SNAQ) ( 74 , 75 ) and the Rapid Cognitive Screen (RCS) ( 76 ) to provide a more comprehensive geriatric examination, which can be performed by a primary care provider or other allied health care professionals (Figure 1 ). The complete RGA can be carried out in under 5 minutes ( 77 ) and is available as an App which was utilized by the National Lniversity Health System in Singapore ( 78 ). Furthermore, the RGA can be integrated into the Medicare Annual Wellness Visit ( 79 ).…”
Section: Management Of Frailtymentioning
confidence: 99%
“…The FRAIL screen has been integrated with 3 other tests: The SARC-F (Sarcopenia) ( 2 , 73 ), the Simplified Nutrition Appetite Questionnaire (SNAQ) ( 74 , 75 ) and the Rapid Cognitive Screen (RCS) ( 76 ) to provide a more comprehensive geriatric examination, which can be performed by a primary care provider or other allied health care professionals (Figure 1 ). The complete RGA can be carried out in under 5 minutes ( 77 ) and is available as an App which was utilized by the National Lniversity Health System in Singapore ( 78 ). Furthermore, the RGA can be integrated into the Medicare Annual Wellness Visit ( 79 ).…”
Section: Management Of Frailtymentioning
confidence: 99%
“…The FRAIL screen has been integrated with 3 other tests: The SARC-F (Sarcopenia) ( 2 , 73 ), the Simplified Nutrition Appetite Questionnaire (SNAQ) ( 74 , 75 ) and the Rapid Cognitive Screen (RCS) ( 76 ) to provide a more comprehensive geriatric examination, which can be performed by a primary care provider or other allied health care professionals (Figure 1 ). The complete RGA can be carried out in under 5 minutes ( 77 ) and is available as an App which was utilized by the National University Health System in Singapore ( 78 ). Furthermore, the RGA can be integrated into the Medicare Annual Wellness Visit ( 79 ).…”
Section: Management Of Frailtymentioning
confidence: 99%
“…It is suggested that at discharge from hospital and at 3 months discharge from hospital all COVID-19 patients are screened for frailty with the FRAIL test ( 48 51 ), sarcopenia with the SARC-F ( 52 – 55 ), anorexia with the SNAQ ( 56 , 57 ) and cognitive failure with the Rapid Cognitive Screen (RCS) ( 58 ). These tests are simply combined into the RAPID Geriatric Assessment ( 59 , 60 ) and are available in an App form ( 61 ). Persons who screen positive and need to receive appropriate therapy which needs to be provided free to the individual.…”
Section: Rehabilitationmentioning
confidence: 99%